ผลของแคลเซียมโบรอนและจิบเบอเรลลิคแอซิดต่อการพัฒนาคุณภาพผลผลิตพลับพันธุ์ฟูยู - เหลาพะวัง, สายน้ำผึ้ง; ชุมภูคำ, เจนจิรา; นะมิกิ, อิษยา; เมฆตรง, วีระศรี; กฤษณพุกต์, กฤษณา (Thai Journal of Science and Technology, 2019)
Abstract ‘Fuyu’ persimmon has a high marketing potential but low yield and small fruit size. The objective of this study is to improve quality of ‘Fuyu’ persimmon by spraying 10 mg/L gibberellic acid (GA3) at blooming stage, calcium boron (CaB) [50 mg/L Ca(NO3)2 and 5 mg/L Na2B4O7] and calcium boron with gibberellic acid (CaB + GA3) at 1 week before blooming stage, blooming stage and 1 week after blooming stage. It was found that ‘Fuyu’ persimmon sprayed with GA3 had lowest seed. Persimmon sprayed with CaB, GA3 and CaB + GA3 had fruit weight and fruit firmness more than that of the control. Furthermore, ‘Fuyu’ persimmon sprayed with CaB showed the highest chroma of peel and pulp. Keywords: persimmon; fruit firmness; fruit weight